PANDANGAN HUKUM ISLAM TERHADAP ADAT MADDOJA DI KECAMATAN BAROKO KABUPATEN ENREKANG - Adnan, Rahmawati (IAIN Palopo, 2024)
The subject of this study is the process of implementation and views of Islamic law on the Madoja custom in Baroko District, Enrekang Regency. This type of research uses a kind of field research with qualitative research methods, namely direct research into the field to visit the object of research, while the data sources used in this study are primary and secondary data, the data collection techniques in this study are observation, interviews, and documentation, data management techniques, namely editing, and concluding. The subject matter consists of two sub problems, namely how is the procession in the implementation of the Madoja tradition carried out by the people of Fort Alla Utara Village, Baroko District, Enrekang Regency and how does Islamic law view the Madoja custom in Baroko District, Enrekang Regency. The results of this study show that the process of implementing the Madoja Tradition starts from the event of Pamula kamatean, Mak randuk bongi, Mak bongi pitu, Mak papura and Mak patang pulo after the death of the mayit. In implementing the Madoja Tradition, several stages of traditional processions are considered sacred and essential to be carried out, namely Mapopellao kandean (Lowering the Spirit), which is the process of carrying the spirit to the afterlife. Thus, implementing the Madoja tradition is categorized as permissible as long as it is in line with Islamic law and the benefits contained in its implementation.